Analisis Hasil Perbandingan Penerapan Metode Heuristic Evaluation Menggunakan Persona dan Tanpa Persona (Studi Kasus : Situs Web Female Daily) - Atika Baladina; Ismiarta Aknuranda; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
This study aims to analyze the differences in results of usability evaluation using Heuristic Evaluation method without Persona and with Persona. In this study, there are three main steps to get the desired results: making Persona, heuristic evaluation and the analysis of the results, both without Persona and with Persona. The making of Persona in this study using qualitative Persona which start with interviewing 20 respondents who were users of Female Daily Network website. This interview aims to understand users' characteristics and behaviors when accessing the website. Data obtained from interviews is used to build Persona. Website then evaluated using heuristic evaluation method without Persona and heuristic evaluation method with Persona. Each evaluation is carried out by three different evaluators. Results of evaluations from both methods then compared for analysis. Comparison seen from the difference in number of problem findings, graph of the number problems found from each evaluator, problem categories based on severity rating, and differences in heuristic categories that were successfully met from the problems found. The results of this study indicate that evaluations using Heuristic Evaluation method with Persona managed to identify more usability problems than Heuristic Evaluation method without Persona.